2019
DOI: 10.1088/2058-9565/ab2819
|View full text |Cite
|
Sign up to set email alerts
|

Towards a realization of device-independent quantum key distribution

Abstract: In the implementation of device-independent quantum key distribution we are interested in maximizing the key rate, i.e. the number of key bits that can be obtained per signal, for a fixed security parameter. In the finite size regime, we furthermore also care about the minimum number of signals required before key can be obtained at all. Here, we perform a fully finite size analysis of device independent protocols using the CHSH inequality both for collective and coherent attacks. For coherent attacks, we shar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 135 publications
(465 reference statements)
0
50
0
Order By: Relevance
“…Tighter bounds on F (ρ E|00 , ρ E|11 ) should give similar results in DIQKD, hence this would be an important next step. Alternatively, one could analyse the finite-key security [3,39,40]. Since our approach yields explicit bounds [21] on the entropies in Eq.…”
Section: 3%mentioning
confidence: 99%
See 1 more Smart Citation
“…Tighter bounds on F (ρ E|00 , ρ E|11 ) should give similar results in DIQKD, hence this would be an important next step. Alternatively, one could analyse the finite-key security [3,39,40]. Since our approach yields explicit bounds [21] on the entropies in Eq.…”
Section: 3%mentioning
confidence: 99%
“…Since our approach yields explicit bounds [21] on the entropies in Eq. (1), it could in principle be extended to a finite-size security proof against collective attacks by using the quantum asymptotic equipartition property [41], following the approach in [40]. However, this approach is likely to require a large number of rounds to achieve positive key rates, which would pose a challenge for practical implementation.…”
Section: 3%mentioning
confidence: 99%
“…high Bell violation and low bit error rate), which in practice requires ultra-low-noise setups with very high detection efficiencies; though in recent years the gap between the theory and practice has been significantly reduced owing to more powerful proof techniques 9 , 10 , 13 and the demonstrations of loophole-free Bell experiments 14 17 . The present gap is best illustrated by Murta et al 18 , whose feasibility study showed that current loophole-free Bell experiments are just short of generating positive key rates assuming the original DIQKD protocol 2 , 3 (see the dashed line in Fig. 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…A second motivation is more practical. Demonstrating a working and secure device-independent protocol remains technologically highly challenging [16,17] as it requires entangled particles to be distributed and detected with low noise and a high detection rate over long distances. Our results lead to two refinements to the CHSH-based protocol that ease these demands.…”
Section: Introductionmentioning
confidence: 99%